Associating Teaching Competence and Grades in Method Subjects among Student Teachers as Basis for Curricular Revision - Lijueraj J. Cuadra; Bayron Barredo (JPAIR Institutional Research Journal)
Competence, ability, and knowledge of student teachers could affect their performance as teachers. Thus, teacher education institutions should focus on preparing student teachers to be competent and efficient in managing today's classrooms. The study examined the correlates of teaching competencies among student teachers of the College of Education at the Visayas State University (VSU), Philippines. Branching Diagram Analytical Technique (BRANDT) was used to describe the relationship between the student teaching performance and performance of the method subjects. A bivariate correlation was also applied to find the relationship among student performance, hobbies, skills, organizations, and grades in methods subject. Additionally, Analysis of Variance (One-way ANOVA) was utilized to interpret further and analyze the data. The results showed that there's a significant relationship among student teaching performance, some personal attributes, and grades in the method subjects. Therefore, the number of organizations the students were involved in was highly related to their ratings in the method subjects. The student teachers' knowledge and application of educational principles and methods were relevant in their teaching competence. However, it is recommended that the relationship between teaching performance and competence should be further evaluated.